Turnaround time and barriers to treatment of newly diagnosed cancer in Uganda: a mixed-methods longitudinal study - Kibudde, Solomon; Namisango, Eve; Bbaale, Joy; Orem, Jackson (African Health Sciences, 2022)
Cancer represents a growing public health concern. Late-stage at diagnosis, limited access to effective treatment, and loss to follow-up are responsible for dismal outcomes. To describe care pathways, turnaround times, and identify barriers to timely initiation of cancer treatment Using a sequential mixed-methods design involving focus group discussions, we followed up 50 participants between January, and June 2018. We computed the median observed turnaround time to treatment (TTT) at each care step and reported delay as deviations from the proposed ideal turnaround times. The ideal TTT with either chemotherapy, or radiotherapy, or surgery was 8, 14, and 21 days respectively. At a median follow-up time of 35.5 days (IQR 17-66), only 29 of the 50 study participants had completed all steps between registration and initiation of treatment, and the observed median TTT was 16 days (9 – 22 days) for chemotherapy, and 30 days (17 – 49 days) for radiotherapy, reflecting a significant delay (p-value = 0.017). Reported barriers were; shortage of specialists, patients required visits to outside facilities for staging investigations, prohibitive costs, poor navigation system and time wastage. When compared to the recommended ideal turnaround time, there was significant institutional delay in access to chemotherapy and radiotherapy attributed to multiple external and internal healthcare system barriers. Keywords: Turnaround time; steps; barriers; waiting time; cancer; Uganda.